2019
DOI: 10.15171/icnj.2019.19
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Group Counseling Based on Metacognitive Therapy and Dialectic Behavior Therapy on Reducing Anxiety in Boy Adolescent of Divorce

Abstract: Background: Anxiety among teenagers may disturb their life, and it is no controlling results in severe problems. Therefore, the present research was designed and conducted by the aim of investigating the effectiveness of group counseling training based on metacognitive therapy & dialectic behavior therapy on reducing anxiety in boy adolescent of divorce. Methods: The present research conducted by quasi-experimental method and used a pretest-posttest with control group design. The statistical population of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Self-compassion involves caring for oneself in the face of perceived shortcomings and difficulties; in such A E-ISSN: 2981-2526 a way that painful and uncomfortable feelings are not avoided, but rather approached with kindness, understanding, and a sense of shared humanity (Braehler & Neff, 2020). In this context, the results of various studies have shown that Compassion-Focused Therapy is effective on experiential avoidance in adolescents (Karimi et al, 2020), experiential avoidance and cognitive fusion (Farokhi et al, 2018), post-traumatic growth in women (Kiarsi et al, 2021;Navab et al, 2019), post-traumatic growth after a romantic breakup (Karimi et al, 2020;Navab et al, 2019), post-traumatic growth in women with cancer (Sadeghpour et al, 2020), cognitive-behavioral avoidance in depressed adolescents (Bakker, 2017), increased post-traumatic growth in sexual abuse victims (Ha et al, 2019), reduction of experiential avoidance and increased flexibility (Godini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Self-compassion involves caring for oneself in the face of perceived shortcomings and difficulties; in such A E-ISSN: 2981-2526 a way that painful and uncomfortable feelings are not avoided, but rather approached with kindness, understanding, and a sense of shared humanity (Braehler & Neff, 2020). In this context, the results of various studies have shown that Compassion-Focused Therapy is effective on experiential avoidance in adolescents (Karimi et al, 2020), experiential avoidance and cognitive fusion (Farokhi et al, 2018), post-traumatic growth in women (Kiarsi et al, 2021;Navab et al, 2019), post-traumatic growth after a romantic breakup (Karimi et al, 2020;Navab et al, 2019), post-traumatic growth in women with cancer (Sadeghpour et al, 2020), cognitive-behavioral avoidance in depressed adolescents (Bakker, 2017), increased post-traumatic growth in sexual abuse victims (Ha et al, 2019), reduction of experiential avoidance and increased flexibility (Godini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety disorders are one of the most common disorders among adolescents. 1 Generalized anxiety disorder is a chronic anxiety disorder characterized by severe and uncontrollable anxiety and associated physicalpsychological symptoms. These individuals report degrees of performance impairment ranging from job focus to interpersonal relationships.…”
Section: Introductionmentioning
confidence: 99%